2009
DOI: 10.1182/blood.v114.22.222.222
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of Bioencapsulated Factor IX Protects From Inhibitor Formation and Anaphylaxis in Protein Replacement Therapy for Hemophilia B.

Abstract: 222 While the incidence of inhibitor formation against the infused coagulation factor is overall relatively low in factor IX-deficiency (1–4% of patients), 9–23% of patients with severe hemophilia B form inhibitors, which seriously complicates treatment. Factor IX (F.IX) inhibitors tend to be high titer and not effectively eliminated by immune tolerance induction protocols, and are often associated with serious anaphylactic reactions. Inhibitor formation and anaphylaxis is more typical for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies using mucosal exposure to the immunogenic C2 domain have shown that tolerance to C2 can be achieved through this strategy, but when the mice are exposed to full‐length FVIII, inhibitory antibodies develop [34]. Very recent preliminary evidence suggests that FIX made in transgenic plants can mediate tolerance and prevent fatal anaphylactic episodes after oral administration [35].…”
Section: Tolerance Mechanisms In Animal Models (David Lillicrap)mentioning
confidence: 99%
“…Studies using mucosal exposure to the immunogenic C2 domain have shown that tolerance to C2 can be achieved through this strategy, but when the mice are exposed to full‐length FVIII, inhibitory antibodies develop [34]. Very recent preliminary evidence suggests that FIX made in transgenic plants can mediate tolerance and prevent fatal anaphylactic episodes after oral administration [35].…”
Section: Tolerance Mechanisms In Animal Models (David Lillicrap)mentioning
confidence: 99%
“…These investigators have explored pharmacological methods for expanding the Treg population, which could prove to be useful either for gene transfer or ITI protocols [42,43]. Other strategies for inducing tolerance prior to inhibitor development have included the use of oral/nasal tolerance regimens [44,45] and administration of a retroviral vector expressing the transgene to the liver in the neonatal period [46,47].…”
Section: Risk Factors For Inhibitor Developmentmentioning
confidence: 99%